Integrated pest management: potential, constraints and challenges - Koul, O.; Cuperus, G. W.; Cuperus, G. W.; Dhaliwal, G. S.; Dhaliwal, G. S.; Koul, O. (Wallingford :CABI Publishing, 2004)
This book addresses many of the key issues surrounding integrated pest management (IPM), particularly of insects. Topics include the pesticide paradox in IPM; risk-benefit analysis; transgenic crops in IPM; and consumer response to IPM. This book will be of great use to researchers in crop protection, entomology and pest management.
Keywords: FF020 - Plant Breeding and Genetics; FF620 - Plant Pests, (New March 2000); HH300 - Integrated Pest Management; HH405 - Pesticides and Drugs; Control, (New March 2000); UU485 - Social Psychology and Social Anthropology, (New March 2000); WW100 - Genetic Engineering, Gene Transfer and Transgenics, (New June 2002)